Bir konfeksiyon otomasyon yazılımı - Torgaloz, Ferhat (Fen Bilimleri Enstitüsü, 1997)
Günümüzde bir çok üretim ve hizmet sektöründe üretim sürecinin tamamlanması için sipariş değerlendirme, kavramsal çalışma, tasarım, öncül örnek, üretim aşamaları ve gereksinimleri, üretim ve kalite kontrol gibi bir dizi çalışmanın yapılması gerekir. Bu çalışmalar genellikle uzun zaman alan ve pahalı olan emeğe dayalı işlemlerdir. Daha hızlı, daha ucuz ve daha güvenilir sonuçlar elde edebilmek için üretimin çeşitli aşamalarında çeşitli şekillerde bilgisayar sistemlerinin, lojik tasarımların ve ölçme sistemlerinin kullanılması o sistemin otomasyonu anlamına gelir. Bu otomasyon sistemi bazen Bilgisayar Destekli Tasarım, bazen Bilgisayar Destekli Üretim veya bazen de her iki yöntemi içeren bir çözüm olabilir. Konfeksiyon sektöründe ise Üretim iş Planlaması, Üretim Takibi, Stok Takibi gibi bir çok üretim aşaması mevcuttur. Bu tezin konusunu oluşturan çalışma konfeksiyon sektöründe kullanılmakta olan model tasarım, şenlendirme ve pastal planı hazırlama tasarım aşamalarıdır. Hem emek yoğun ve hem de insan beğenisine dayalı bir çalışma olması nedeniyle istenen sonuçlar elde edilene kadar defalarca tekrarlanması gerekmektedir. Her bir deneme ek bir masraf ve zaman demektir. Bu değerler de üretim maliyetlerini arttıran faktörlerdir. Çoğu zaman bu ek masraflar altında maliyetler artmakta veya istenen sonuçlar sağlanana kadar deneme yapılmamakta ve ucuz fakat sevimsiz sonuçlar elde edilebilmektedir. Bu şartlar altında böyle bir üretim aşamasını bilgisayar desteği ile gerçeklemek konfeksiyon sektöründe önemli bir atılım olmaktadır. Bilgisayar desteği ile sağlanan sistem çözümleri yukarı da değindiğimiz gibi çok daha ucuz, daha hızlı ve defalarca tekrarlanabilirlik özelliklerine sahiptir. Bu özellikler ise maliyeti doğrudan etkileyen faktörlerdir. Tez kapsamındaki ürün sayesinde konfeksiyon firması ihtiyaca uygun tasarımı model tasarım modülünde gerçekler. Pervaz, pile, çıt, dikiş payı gibi konfeksiyon sektörüne özgü özellikleri modeli oluşturan kalıp parçalan üzerinde tanımlayabilir. Tasanmcı isterse noktalar ve bunların arasındaki düz ve eğri çizgilerden oluşan kalıplar üzerinde nokta ekleme, silme, döndürme, aynalama, simetri, kesme, birleştirme gibi bir takım geometrik işlemleri gerçekleyebilir. Tasannu biten model temel beden olarak tanımlanır ve diğer türetilmek istenen beden setleri ve bu setler arası geçişler tanımlanmak sureti ile şenlendirme işlemi gerçeklenebilir. Tasanmı ve şenlendirmesi biten modeller arasında aym kumaş malzemesi ile üretilecek olan modeller bir pastal siparişi şeklinde düzenlenir. Bu işlemin ardından eni ve boyu belli kumaş malzemesi üzerinde modellerin pastal yerleşim planı hazırlanır. Pastal yerleşim planı tasarlanırken önemli sorun modeli oluşturan kalıpların minimum kayıp ile kumaş malzemesi üzerine yerleşimlerinin düzenlenmesidir. Kalıplann yerleşim planı ya fare yardımı ile tek tek stoktan alıp kumaş malzemesine taşıma şeklinde ya da otomatik pastal tasarım algoritmalan sayesinde gerçeklenir. Tez kapsamında ise bu otomasyon yazılımının oluşturulmasında kullanılan Microsoft Windows işletim sistemi, Nesneye Yönelik Programlama ( Object-Oriented Programming ) ve Microsoft Visual C++ programlama ortamı gibi tekniklerin ve yaklaşımlann kısaca tanımı ve bu Otomasyon Sisteminin tanıtımı yapılmaktadır. x

The Experiences and knowledges, that advanced increasingly and were transmited parent to child, have exposed the present technologies in the course of time. Semi conductor tranzistor technology were developed at the beginning of 1970s. As a result of this, the science supplied that developments not possible to be realized or not economical are accomplished. The level attained finally at the technological development is computer era. The using of computers at the works supplies to be obtained more rapidly the more reliable results. The making operations to the usual way needs the certain experiments that are achieved after a long time. But the making the same operations by computer needs the more little experiments. The cause of this is that the application gives users information in the common of working and presents users explanatory information in the various level of working. In addition, the computers can store information in the requested form at the appropriate time. The users can access later and use again this information. In this way, the users can obtain the different working instance. Such a structure supplies a flexible working way. The computer aided design and computer aided management that is such advantages is used at the textile sector the same way to other management sectors. The first researches at this subject started on America at 1960s. They converted an extensive trade, because the France and Espanol firm went the market. Also at our country, these researches weren't developed. Therefore firms buyed the applications that produced at the other country and used these applications. Our textile sector needed to develop and tended the research works. As a result of this, our porject was emerged. This project is developed in the Microsoft Visual C++ Integrated Development Environment. Its data is stored in the Microsoft Access Database Management System. Visual C++ has fully Windows Programming and Object-Oriented Programming features. Because of this, first I introduce what the Windows Programming and Object-Oriented Programming are and what their features are. And then I introduce the Textile Automation Software that is subject to my Master thesis. xu Windows Programming Microsoft Windows has emerged as the most popular graphical user interface environment for MS-DOS. For the user, Windows provides a multitasking graphical-based windowing environment that runs programs espically designed for Windows. Programs written for Windows have a consistent appearance and command structure, and are thus often easeir to learn and use than conventional MS-DOS programs. Users can easily switch among different Windows programs and exchange data between them. Windows also provides an easy-to-use icon-based Program Manager for running programs as well as File Manager and Print Manager for file maintenance and printer-queue management. Altough Windows exists primarily to run applications especially written for the environment, Windows can also run many programs written for MS-DOS. Of course, these programs cannot take advantage of many Windows feature, but in some cases they can be windowed and multitasked alongside Windows programs. For the program developer, Windows provides a wealth of built-in routines that allow the use of menus, dialog boxes, scroll bars, and other components of a friendly user interface. Windows also contains an extensive graphics programming lanuage that includes the use of formatted text in a variety of fonts. Programmers can treat the keyboard, mouse, video display, printer, system timer, and RS-232 communication ports in a device-independent manner. Windows programs run the same on a variety of hardware configurations. Windows provides considerable advantages to both users and programmers over the conventional MS-Dos environment. The benefits to users and the benefits to program developer are really quite similar, because the jobs of a program developers is to give users what they need and want. Windows makes this possible. Windows is a graphical user interface (GUI), sometimes also called a "visual interface" or "graphical windowing environment". All graphical user interface make use of graphics on a bitmapped video display. In a graphical user interface, the video display itself becomes a source of user input. The video display shows various grahical objects in the form of icons and input devices such as buttons and scroll bars. Using keyboard (or, more directly, a pointing device such as a mouse), the user can directly manipulate these objects on the screen. Graphics objects can be dragged, buttons can be pushed, and scroll bars can be scrolled. Under Windows, every program in effect becomes a RAM-resident popup. Several Windows programs can be displayed and running at the same time. Each program occupies a rectangular window on th screen. The user can move the windows aorund on th screen, change their size, switch between different programs, and transfer data from one program to another. An operating system cannot implement multitasking without doing something about memory management. As new programs are started up and old ones terminate, xiu memory can become fragmented. The system must be able to consolidate free memory space. This requires the system to move blocks of code and data in memory. Windows is a graphical interface, and Windows programs can make full use of graphics and formatted text on both the video display and printer. Programs written for Windows do not directly access the hardware of graphics display devices such as the screen and printer. Instead, Windows includes a graphics programming language (called the Graphics Device Interface, or GDI) that allows the easy display of graphics and formatted text. Windows virtualizes display hardware. A program written for Windows will run with any video board or any printer for which a Windows device driver is available. The program does not need to determine what type of device is attached to the system. Object-Oriented Programming Object,Oriented programming - sometimes fondly refered to as OOP - is a hot topic int the computer industry. It is a language that tries to solve problems in a new and better way by dividing programs into objects that have meaningful relationships with each other rather than into largely unrelated aggregations of functions and data. When you write an object-oriented program, your first task is to design a data form that corresponds to the essential features of your problem. Then you must create a set of procedures, or methods, that manipulate that data to solve the problem. If you're writing program designed to solve more than one problem, you can create sets of data structures, and methods that work together, and then you can arrange those structures and behaviours into relationships and hierarchies that also work well together. Simply stated, you can break a problem down into objects that have built- in data and built-in behaviours. Then you can group those building blocks into a sensible arrangement that seem to be suited to solving your problem. If your fist attmpt to solve the problem doesn't work as well as expected, you can rearrange the buildin blocks that make up an object-oriented program into different arrangement. Object-oriented langauges let you do that easily and conveniently because the objects that make up an object-oriented program are more independent than the procedures that make up a procedural program, and can therefore be rearranged and moved around more freely. Furthermore, when you have designed an object-oriented program that work, you can reuse the program's code in other applications much more easily and convenently than you can when you're working with procedural programs such as C and Pascal. Thus, when you write programs into an object-oreinted language, you don't have to start from scratch every time you get a new program to write or a new problem to solve. For almost 50 years now, software designers have used procedural and structural paradigms to create most kinds of computer programs. Procedural and structural XIV paradigms take a top-down, or structured, approach to program design. A task is partitioned into subtasks; those subtasks are further partitioned into still smaller subtasks, and so on until the main task has been divided into subtasks that are simple enough to be programmed in a conventional procedural language. A object-oreinted program is made up of reusable objects that are relatively independent of other objects, yet have characteristics that are inherited from other objects and also have characteristics that can be passed on to other objects. This paradigm is said to have more in common with the standard paradigms used in other engineering disciplines than does the procedural paradigm that is used for program construction by conventional procedural languages. It's important to note that OOP does not repudiate the procedural paradigm, but enhances it. Object-oriented programs makes use of procedure, but those procedures are encapsulated within objects, along with data that the procedures manipulate. Thus, object-oriented technology has fundamentally changed - but has not destroyed - the old procedural programming paradigm. Other terms often encountered in OOP circles include these : Objects : Ann object is a user-defined data type that resembles a C-style struct, but contains both data and functions that can manipulate that data. The data fields contained in an object are usually called member variables, but are sometimes refered to as data member. The functions contained in an object are usually called member functions, but are sometimes called methods. In an object-oriented langauge, the data and procedures that are grouped together to form objects can be used together to create more objects. In C++, inheritance lets you create objects that inherit properties of other objects. And objects can access data and call functions that are members of other objects. Classes : In C++, every object is an instance of a user-created data type called class. A class is a framework that sets up the architecture of an object. An object is an instance of a class. Therefore, the act of creating an object is called instantiating the object. Data encapsulation : In C++, The member functions declared within the definition of a class can access all member variables that belong to the same class. However, an object can safeguard its member variables from being accessed ar altered from elsewhere in a program. Tha ability that an object has to conceal its data from other parts of a program is called encapsulation. Data abstraction : When you design a class in C++, you can conceal the details of how data is represented and modified inside the objects that belong to a class. Data abstraction is what lets the calling function ignore the details of how data types are represented inside objects and lets it concentrate instead on the job that it wants done. Inheritance : In an object-oreinted language, you can create a new class from any existing class by modifying the properties of existing class. The usual purpose for deriving one class from another is to create a more specialized class. The derivation XV of one class from another class is called inheritance. A class from which other classes are derived is called a base class, and classes that are derived from (or inherit from) a base class are called derived classes. The immediate base classs of a derived classs is called a parent class. Multiple Inheritance : Some object-oriented languages - including C++ - support multiple inheritance. In a language that supports multiple inheritance, an object can inherit properties from more than one class. Polymorphism : In biology, the occurrence of different properties in individual organisms, or in organisms in the same species, is called polymorphism. In a C++ program, polymorphism lets you create a family of classes with behaviours that vary, according to what is appropriate for each class. If you call a member function of a particular object, your call may have one result, and if you issue the same call to a a member function of another object, the result may be completely different. Pattern Design, Grading and Markermaking The first applications that the computer aided pattern design researches are based on is started by Howard Hughes, a famous and well-known American. He started first the development program that contains the computer aided hardware related to 2 D application. The basic idea of bis research is that any drawing and cutting operation can be accomplished on the two dimensional surface. This research is beginned on the Hughes Research Company at 1960 year. At the same year, a laser circle is introduced. At 1968 after eight years, Hughes that work together Genesco successfully developed a computer aided cloth cutting. It worked to the laser ray and had more speed and truth than the conventional methods. It is awared of that this developed technological evoluation can allow us to make easier and faster the producting of ready-made suits. Hughes designed a system easily accomplishing the "grading" and "markermaking",that is most difficult production process, with the support of Autographies which had experiment a long time. This system had the very powerful main computer produced Hewlect Packard. It which is the first computer aided management (CAM) system is called AMI. Hughes Apparel System developed continously and sold the AMI throughout the ten years. Gerber a American firm bought it at 1978-9 years. Gerber had the experiment about the computer aided machine cutting the bulk cloth. It also developed the system which it had the patent and the copy-right. The Hughes's AMI a Computer Aided Design and Computer Aided Management (CAD / CAM) for the markermaking and pattern design was used in order to cut the bulk cloth by Gerber. Gerber developed the AMI and released the AM5 more modern than the AMI. Both systems worked on the main computer of Hewlect Packard and also can worked on the computer of IBM. XVI At themoment, the systems of American Camsco and France Lectra are built. Lectra started the researches at 1975 and released their first systems at 1978. They had the experiments about the Lazer preparatory and sold the lazer systems which can cutted the carton patterns, or the one layer cloth or the leather. Also both firm producted the Computer Aided Management systems (grading and markermaking) and tried to develop the Computer Aided Design system (graphics and cloth pattern design software) that works with together CAM. Gerber bought Camsco firm in order to terminate the competition and monopolize in the market which was weak at the beginning of 1980s. At this case, two big firm Gerber and Lectra had the small trade. Their trade was rapidly increased after the two firm done the hard and serious sale program. After his moment, the trade was extensive and other computer firms participated and started the research about this subjects. Espanol Investronica participated powerfully this market. The other firms followed them. In the final, the researches and the CAD/CAM systems about this pattern design, grading and markermaking have the situation at present. They are similar together »because they based on the basic idea which Hughes introduced at 1960s. In the course of time, Our textile sector has developed and started to be the world wide trade. Because of this, they have needed to do the researches and suppurted the working at this subject for not the back of other firms and countries. They have tried to produce and developed the native computer automation systems. Our project is emerged at the result of such a working. xvu
A textile automation software
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Bilgisayar yazılımları; Hazır giyim endüstrisi; Kalite kontrol; Otomasyon; Sipariş; Computer softwares; Ready made wear industry; Quality control; Automation; Order; Production